2015
DOI: 10.2135/cropsci2015.02.0077
|View full text |Cite
|
Sign up to set email alerts
|

Confirming and Identifying New Loci for Rice Blast Disease Resistance using Magnaporthe oryzae Field Isolates in the US

Abstract: Quantitative trait loci (QTL) play important roles in controlling rice blast disease. In the present study, 10 field isolates of the races IA1, IB1, IB17, and IC1 of US rice blast fungus Magnaporthe oryzae collected in 1996 and 2009 were used to identify blast resistance QTL with a recombinant inbred line (RIL) population consisting of 227 F7 individuals derived from the cross of rice (Oryza sativa L.) cultivars Lemont and Jasmine 85. Jasmine 85 is an indica cultivar that is moderately resistant, and Lemont is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Ying et al (2012) identified a QTL qOle8 for oleic acid in the proximity of RM1148 on chromosome-8 by analyzing an F 2 population. Later close linkage (4.4 cM) of RM25 and RM1148 was established by Xing et al (2015) during the tagging of a new rice blast resistance gene in a RIL population. Thus, identification of RM25 as a significantly associated marker for oleic acid content in these rice landrace has immense opportunity to use this marker for the MAS program in the future breeding for high oleic acid content in rice bran.…”
Section: Discussionmentioning
confidence: 99%
“…Ying et al (2012) identified a QTL qOle8 for oleic acid in the proximity of RM1148 on chromosome-8 by analyzing an F 2 population. Later close linkage (4.4 cM) of RM25 and RM1148 was established by Xing et al (2015) during the tagging of a new rice blast resistance gene in a RIL population. Thus, identification of RM25 as a significantly associated marker for oleic acid content in these rice landrace has immense opportunity to use this marker for the MAS program in the future breeding for high oleic acid content in rice bran.…”
Section: Discussionmentioning
confidence: 99%
“…6). Except for the population Sakha 104 × IRBL9-W the ratio was 3 positive: 1 negative with all the primers [51][52][53][54][55][56]. However, the data for F 2 generations were categorized into two groups according to segregation ratios.…”
Section: Genetic Analysis In F 2 Populationmentioning
confidence: 99%
“…RM289, RM590 and RM202 related for (R-genes Pi 26(t), Piz (the most effective genes under this study) and R-gene Piy(t), respectively). The same markers were related for R-genes (Goncharova, et al,2020, Eizenga, et al,2009, Xing, et al, 2015and Wang, et al, 2014, RM163 and RM3394 related for identified blast resistance to blast genotype (Hasan, et al, 2018 andWang, et al, 2015), as show in Table ( 7). Six SSR markers (RM3392, RM289, RM6467, RM23001, RM205 and RM5313) were determined for grain yield of thirteen promising lines.…”
Section: Molecular Analysismentioning
confidence: 99%